Sensitization of CD4+ T Cells to Coagulation Factor VIII: Response in Congenital and Acquired Hemophilia Patients and in Healthy Subjects - Reding, Mark T.; Wu, Huiyun; Krampf, Mark; Okita, David K.; Diethelm-Okita, Brenda M.; Christie, Beverly A.; Key, Nigel S.; Conti-Fine, Bianca M. (Thrombosis and Haemostasis, 2000)
Antibodies (Ab) that inhibit factor VIII (fVIII) may develop in patients with hemophilia A and rarely in individuals without congenital fVIII deficiency (acquired hemophilia). Synthesis of fVIII inhibitors requires CD4+ T cells. We investigated the proliferative response of blood CD4+ cells from 11 patients with congenital or acquired hemophilia and 12 healthy subjects, to recombinant human fVIII, and to pools of overlapping synthetic peptides spanning the sequences of individual fVIII domains. All patients had CD4+ cells that responded to fVIII. The intensity of the responses fluctuated over time: several patients had brief periods when they did not respond to fVIII. All healthy subjects had transient CD4+ responses to fVIII, that were significantly lower than those of hemophilia patients. Also, healthy subjects responded to fVIII less frequently and for shorter periods than hemophilia patients. All patients and healthy subjects recognized several fVIII domains: the A3 domain was recognized most strongly and frequently. The transient sensitization of CD4+ cells to fVIII in healthy subjects suggests that inadequate tolerization of CD4+ cells to fVIII, due to lack of endogenous fVIII, is an important factor in the development of clinically significant anti-fVIII antibodies in hemophilia A.
Keywords: Immune response; T cells; factor VIII; inhibitors